2009
DOI: 10.1002/pros.20931
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the sesquiterpene lactone parthenolide on prostate tumor‐initiating cells: An integrated molecular profiling approach

Abstract: Recent evidence suggests tumor-initating cells (TICs), also called cancer stem cells, are responsible for tumor initiation and progression; therefore, they represent an important cell population for development of future anti-cancer therapies. In this study, we show that the sesquiterpene lactone parthenolide (PTL) is cytotoxic to prostate TICs isolated from prostate cancer cell lines: DU145, PC3, VCAP and LAPC4, as well as primary prostate TICs. Furthermore, PTL inhibited TIC-driven tumor formation in mouse x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 33 publications
(47 reference statements)
3
68
0
Order By: Relevance
“…The STL parthenolide inhibits the activation of the mim-1 gene by v-Myb Kawasaki et al 28 have recently investigated the inhibitory effects of the STL parthenolide on a prostate cancer cell line. They identified several potential targets of parthenolide, one of which was the transcription factor c-Myb.…”
Section: Resultsmentioning
confidence: 99%
“…The STL parthenolide inhibits the activation of the mim-1 gene by v-Myb Kawasaki et al 28 have recently investigated the inhibitory effects of the STL parthenolide on a prostate cancer cell line. They identified several potential targets of parthenolide, one of which was the transcription factor c-Myb.…”
Section: Resultsmentioning
confidence: 99%
“…M21(i(14q)) i(14)(q10) M22(der(15)) add(15)(?::pter-q24::?) M23 (der(15;22)) der (15) Characterisation of a novel cell line (CSQT-2) T Wang et al Moreover, as is well-known, the theory of cancer stem cells argues that a cancer mass is built up by a relatively tiny portion of the total tumour, called cancer stem cells or TIC (Guglielmi et al, 1998;Bansal and Banerjee, 2009;Kawasaki et al, 2009;Tu et al, 2009). The previous research on HCC TICs found that we could separate or enrich HCC TICs through specific staining for cell surface markers, such as CD133, CD90 and EpCAM (Yang et al, 2008a, b;Yamashita et al, 2009;Yeh et al, 2009;Yoshikawa et al, 2009;Zhu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that natural compounds have also been reported to target TICs selectively, with parthenolide (PTL) being the first such compound described (Guzman et al, 2005(Guzman et al, , 2007Steele et al, 2006;Hassane et al, 2008;Kawasaki et al, 2009). PTL is a sesquiterpene lactone found in feverfew (Chrysanthemum parthenium), which has been traditionally used to treat migraine and rheumatoid arthritis and exerts activity as nuclear factor-kB inhibitor, p53 activator (via ubiquitination of MDM2, mouse double minute 2-p53 binding protein homolog), DNMT1 (DNA (cytosine-5-)-methyltransferase 1) inhibitor and promoter of HDAC1 depletion by proteosome degradation (Gopal et al, 2007).…”
Section: Novel Paradigms For Cancer Therapy V Pavet Et Almentioning
confidence: 99%